Pengaruh Gaya Kepemimpinan Transformasional Pelatih terhadap Komitmen Pemain Sepakbola PSKN Kabupaten Timor Tengah Utara - Oki, Kayus Benediktus; Blegur, Jusuf; Rajagukguk, Christin P.M (MANGGUREBE: Journal Physical Education, Health and Recreation, 2021)
This study aims to determine the effect of the coachâ€™s transformational leadership style on the commitment of PSKN football players in North Central Timor Regency. The research method used is non-experimental with a correlational research form with a quantitative approach. The results of the research variable tranformational leadership coach have t count of -0,853 with a significance value of 0,404. This significant value is greater than 0,05, which means that the hypothesis in this study rejects H0 and accepts H1. Thus, it means that the hypothesis â€œTransformational Leadership Style positively has a direct and significant effect on PSKN Soccer Player Commitmentâ€ is accepted. So we can conclude that of transformational leadership style (X) is measured through indicators inspirational motivation, idealized influence, intellectual stimulation and individual consideration greatly affects the commitment (Y) soccer player.